Diagnosis and treatment of internal resorption of teeth: a review of literature and clinical case - M. V. Berkhman (Эндодонтия Today)
Internal resorption is a separate category of diseases of hard tissues of teeth, characterized by the loss of dentine as a result of activation and activity of osteoclasts. The article discuss issues concerning etiology, the prevalence of internal resorption, its diagnosis, emphasise the contribution of computed tomography in the diagnosis and prediction of treatment success, clinical decisions and therapeutic treatment of this disease. Describe modern endodontic treatment methods, including the use of magnification, ultrasound in endodontic treatment, the use of certain materials for temporary and permanent root canal filling. Under these conditions, the prognosis of conservative treatment of internal resorption of dental hard tissues is improved, even if there is a perforation of the walls of the tooth cavity.